Parental-origin-specific epigenetic modification of the mouse H19 gene - Ferguson-Smith, Anne C.; Sasaki, Hiroyuki; Cattanach, Bruce M.; Surani, M. Azim (Nature (London), 1993)
The H19 gene produces an abundant developmentally regulated transcript of unknown function in normal embryos. In the mouse it lies on chromosome 7 and is subject to transcriptional regulation by parental imprinting, which results in the maternally inherited gene being expressed and the paternally inherited gene being repressed. Embryos carrying maternal duplication/paternal deficiency for distal chromosome 7 (MatDi7) therefore express a double dose of H19. Here we examine the parental-origin-specific epigenetic modifications that may be involved in this regulation by comparing CpG methylation and nuclease sensitivity of chromatin in MatDi7 embryos with normal littermates. We show that specific sites in the CpG island promoter and 5' portion of the gene are methylated only on the paternal allele. Furthermore, active maternal alleles in chromatin of MatDi7 embryos are more sensitive and accessible to nucleases. Therefore hypermethylation and chromatin compaction in the region of the H19 promoter is associated with repression of the paternally inherited copy of the gene. Most, but not all, of these sites are unmethylated in sperm, with methylation of the paternal promoter occurring after fertilization. These results contrast with our findings for the closely linked and reciprocally imprinted gene encoding insulin-like growth factor II (ref. 4).